2009
DOI: 10.1111/j.1365-2028.2008.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and fibre: the nutritional value of figs for a small tropical ruminant, the blue duiker (Cephalophus monticola)

Abstract: Tropical forests throughout the world are home to a guild of small ruminants that consume fruit as a substantial portion of their diet. Because the rumen is relatively inefficient at digesting nonstructural carbohydrates and only slowly digests cellulose, the feeding adaptations of frugivorous ruminants are enigmatic. We examined the nutritional value of wild figs to blue duikers, one of the smallest and most frugivorous ruminants, through chemical analyses and a series of digestion trials with six species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“… N: number of samples; X: mean energy gain in kcal/g of dry matter (DM); SD: standard deviation. Values for the different sites are from: 1 this study, 2 [ 84 ], 3 [ 85 ], 4 [ 86 ], 5 [ 87 ], 6 [ 88 ], and 7 [ 31 ]. SBL: Sebitoli; KNP: Kibale National Park (no site specified); KWRA: Kanyawara; NGO: Ngogo, all sites are located in Uganda; RF: ripe fruit; URF: unripe fruit; * missing values in our study (we took RF and URF values instead).…”
Section: Figurementioning
confidence: 99%
“… N: number of samples; X: mean energy gain in kcal/g of dry matter (DM); SD: standard deviation. Values for the different sites are from: 1 this study, 2 [ 84 ], 3 [ 85 ], 4 [ 86 ], 5 [ 87 ], 6 [ 88 ], and 7 [ 31 ]. SBL: Sebitoli; KNP: Kibale National Park (no site specified); KWRA: Kanyawara; NGO: Ngogo, all sites are located in Uganda; RF: ripe fruit; URF: unripe fruit; * missing values in our study (we took RF and URF values instead).…”
Section: Figurementioning
confidence: 99%
“…Crowned lemurs spent more than 33% of their feeding time eaten Moraceae plant family. Species of Moraceae family are rich in tannins (Kendrick et al, 2009). Food items rich in tannins can minimize the possibility of iron absorption (Krishnamani & Mahaney, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that proanthocyanidin concentrations be reported as mass % equivalents of procyanidin dimer. In a recent study of Ficus tannins, we reported a range of 0.15 to 6.40% dry matter of proanthocyanidin, using the acid butanol assay standardized with our Sorghum procyanidin standard (Kendrick et al 2009). If we had used the apple dimer, we would have reported values from 0.21 to 8.96% dry matter procyanidin dimer equivalents.…”
Section: Isolation and Characterization Of Dimers And Trimersmentioning
confidence: 98%